A Semi Analytical Approach to the Solution of Telegraph Equations - Kasumo, Christian (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2024)
In this paper, we apply the semi analytic iterative method to find approximate solutions of telegraph equations. To determine the accuracy and effectiveness of the method, five numerical examples are given and the results obtained are close to the exact solution. Furthermore, the absolute errors produced by our method are closer to zero than those from the other methods used in the literature. The computational simplicity, efficiency, precision and reliability of the semi analytic iterative method has been verified, making it the method of choice for solving a broad variety of linear and nonlinear partial differential equations.